Tinjauan Yuridis Kompilasi Hukum Islam terhadap Nikah Siri dan Implikasinya pada Pemenuhan Hak Keperdataan Perempuan - Asep Mustopa (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The practice of unregistered marriage (nikah siri) remains prevalent in Indonesia and raises serious legal issues, particularly for women as the most disadvantaged party. This study aims to juridically analyze the provisions of the Compilation of Islamic Law (KHI) relating to nikah siri and to identify its implications for the fulfillment of women's civil rights. This study employs a normative legal research method with statutory, conceptual, and case approaches, analyzing primary, secondary, and tertiary legal materials descriptively and analytically. The results reveal three main findings: first, the KHI contains a fundamental normative tension between the recognition of the religious validity of nikah siri under Articles 4 and 14 KHI and the provision of Article 6 paragraph (2) KHI which affirms that marriages conducted outside the supervision of the Marriage Registrar have no legal force; second, this normative tension demonstrably harms women by resulting in the loss of rights to maintenance, marital property, inheritance, divorce claims, and other legal protections, as well as affecting the status of children treated as illegitimate under Article 43 paragraph (1) of the Marriage Law jo. Article 100 KHI; third, the itsbat nikah mechanism under Article 7 KHI as an instrument for restoring civil rights has not been able to serve as a comprehensive solution due to normative limitations and contradictions with SEMA Number 3 of 2018. This study concludes that comprehensive and gender-just regulatory reform is needed to strengthen legal protection for women within Indonesia's Islamic family law system.